IMPROVEMENT OF THE SYSTEM FOR THE ASSESSMENT OF FLEXIBILITY OF 10-12-YEAR OLD MALE ARTISTIC GYMNASTS - Georgi Sergiev (Journal of Applied Sports Sciences)
One of the main purposes of this paper is to perfect sports preparation in artistic gymnastics at the stage of initial sports specialization. This stage coincides with the sensitive period for development of flexibility. This manuscript deals with the issue of flexibility being one of the most significant motor qualities. High level of flexibility development guarantees the successful performance with maximum amplitude of a great number of exercises in artistic gymnastics. The aim of the research was updating the system for tracing the improvement and evaluation of young male gymnasts’ flexibility. The main tasks of the survey were selecting suitable tests for evaluation of the quality flexibility as well as carrying out testing with competitors of all age groups. In the end, a 50-grade scale for evaluation of flexibility was designed along the different indexes (tests). The research was done among 38 male 10-12-year old gymnasts with the help of 8 tests. On this basis specification tables were designed for each test with the use of a 50-grade (point) scale. The specification tables allowed for the quick evaluation of competitors along a certain test right after their measurement. On the basis of the conducted research, testing, collected information and specification tables made, it will be possible to improve the evaluation of the temporary state of competitors’ flexibility at each stage of the preparation. We will also be able to evaluate (notice) the smallest changes (increase) in the indexes during the preparation both in positive and negative aspect.